2018
DOI: 10.1002/fsn3.856
|View full text |Cite
|
Sign up to set email alerts
|

The effect of traditional malting technology practiced by an ethnic community in northern Uganda on in‐vitro nutrient bioavailability and consumer sensory preference for locally formulated complementary food formulae

Abstract: The occurrence of anti‐nutritional constituents in plants is an important factor that negatively affects bioavailability of nutrients and effectiveness of plant‐based foods in complementary feeding in rural areas in developing countries. However, proven methods that improve bioavailability of nutrients and tailored for application in processing complementary foods among rural communities are largely lacking. This study examined the efficacy of a traditional malting technology practiced by the Acholi ethnic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Malting is a popular preparation method traditionally used by Indigenous communities around the world (Alowo et al., 2018). Seeds and legumes have increased energy density and nutrient bioaccessibility when malted (Alowo et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Malting is a popular preparation method traditionally used by Indigenous communities around the world (Alowo et al., 2018). Seeds and legumes have increased energy density and nutrient bioaccessibility when malted (Alowo et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Literature is replete with information on standardized preservation methods such as freezing, canning, pasteurization, refrigeration, high hydrostatic pressure, and microwave cooking (Barrett & Lloyd, 2012). In rural set-ups typical of many developing countries, traditional preservation methods are dominantly used (Hassan et al, 2007;Santhi & Sengottuvel, 2016) and the manner of their application vary from location to location dictated by culture and tradition (Alowo et al, 2018;Asogwa et al, 2017). Due to their significance in offsetting seasonality constraints in food production, the efficacy of The results have demonstrated that the three preservation methods investigated affected the micronutrient content of the vegetables to various extends.…”
Section: Effect Of Traditional Preservation Methods On Micronutrient ...mentioning
confidence: 99%
“…Malting is a food processing technique that has been employed for years to transform and increase the nutritional qualities of millets (Adebiyi et al, 2016;Gowda et al, 2022;Hejazi & Orsat, 2016). Malting practices differ between countries, also vary among communities within a country (Alowo et al, 2018;Bokulich & Bamforth, 2013) and malted cereals are a vital part of the everyday diet of people (Swami et al, 2013;Syeunda et al, 2020). Adetokunboh et al (2022) stated that malting caused an increment in the activities of hydrolytic enzymes, improving total sugars, amino acids content, B-group vitamins and a decrease in starch and dry matter.…”
Section: Introductionmentioning
confidence: 99%